Pengaruh Kepercayaan Terhadap Loyalitas Konsumen Yang Memunculkan Distrust: Universitas Islam Riau - Septian Wahyudi (SISI LAIN REALITA, 2018)
The company certainly wants to increase its sales and increase the number of its customers so that all efforts and methods are carried out, including in building consumer confidence, thus making these consumers become loyal customers or commonly referred to as customers. But on the one hand the trust built by the company actually has a negative impact, namely the emergence of distrust because the frequency of the company offers a variety of products that are sometimes not needed by consumers, this paper is made to answer these phenomena and problems in a concise manner.This research method is by analyzing criticism of several studies about trust that affect consumer loyalty which results in the absence of influence between trust in consumer loyalty.